Genome-wide association study for agronomic and yield-related traits in spring wheat (Triticum aestivum L.) germplasm - Thakur, Ankita; Dhariwal, Raman; Joshi, Arun; Mishra, Vinod Kumar; Sharma, Sandeep; Singh, Mukesh Kumar; Kumar, Sundeep; Vasistha, Neeraj (BioMed Central Ltd, 2025)
Background: Common wheat (Triticum aestivum L.) is one of the most widely grown and consumed cereal crops, but its complicated genome makes it difficult to study how genes affect important agronomic and yield-related traits. Genome-wide association study (GWAS) is a useful method for finding specific loci that control complex agronomic and yield-related traits. Results: The present investigation revealed significant phenotypic variability across the genotypes examined for all traits. The broad sense heritability (H2) for all traits ranged from 0.50 to 0.71 (Env1; 2021–2022) and 0.53 to 0.81 (Env2; 2022–2023). Using two environments’ phenotypic data, and high-throughput single-nucleotide polymorphisms (SNPs) genotypic data of 20,996 markers, we discovered 114 grain-yield-related quantitative trait loci (QTLs) and 300 associated SNP markers. Eighty-five of the identified markers were stable, consistently detected across environments (Env1 and Env2) and combined environment (CE) data, and showed a significant association with 32 different QTLs. The trait with the most associated QTLs (28) was the number of fertile tillers (NFT), with 70 markers. This was followed by 20 QTLs for each, spike length (SL) and spikelet number per spike (SPS), with 69 and 82 SNPs, respectively. Conversely, six SNPs that exhibited association with multiple traits were also identified. Twenty-nine of the total 114 identified QTLs were located in chromosomal positions where at least one marker-trait association had been previously identified. Conclusion: his study has found new SNPs, and useful QTLs that may help us to understand the biological processes behind each studied trait. Further validation in various genetic backgrounds and environments is necessary to confirm the potential utility of the significant alleles found in this study for breeding wheat varieties with improved agronomic and yield-related traits.